Health systems preparedness during COVID-19 pandemic: China and India - Rama V Baru (Wolters Kluwer Medknow Publications, 2020)
This commentary reviews the health systems preparedness during the COVID-19 epidemic in China and India. It provides insight into how nonmedical measures were employed to contain and control the epidemic in Wuhan which was the epicenter. The methods employed by the Chinese provided the roadmap for the countries as the epidemic became pandemic. It provides contrasts in health system preparedness between China and India.